La gestación subrogada en los juzgados de familia de Maynas 2022 - Rodriguez Angulo, Percy (2025)
The thesis aims to describe surrogacy in the family courts of Maynas in 2022 from the three-dimensional theory of law to address the processes related to this legal figure. It consisted of a basic qualitative research approach, with a sample of four focus groups made up of twenty-four lawyers working in the family courts of Maynas. As a result, the participants have the notion that surrogacy is a figure that is not regulated in the Peruvian legal system; however, many individuals or couples, for reasons such as infertility and aesthetic concerns, have resorted to this treatment thanks to advances in medical science. Nevertheless, they hold divided positions: some oppose it because it goes against the principles and values upheld by the Catholic Church, while those in favor argue that it should be regulated to prevent abuse of this practice. Thus, we conclude that they have a multidisciplinary, holistic, or intuitive understanding of surrogacy, which aligns with the authors referenced in this research, prompting the need for regulation to prevent the violation of rights for those involved, particularly the unborn child.